2015
DOI: 10.1007/s00122-015-2546-5
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive phenotypic analysis and quantitative trait locus identification for grain mineral concentration, content, and yield in maize (Zea mays L.)

Abstract: Understanding the correlations of seven minerals for concentration, content and yield in maize grain, and exploring their genetic basis will help breeders to develop high grain quality maize. Biofortification by enhanced mineral accumulation in grain through genetic improvement is an efficient way to solve global nutrient malnutrition, in which one key step is to detect the underlying quantitative trait loci (QTL). Herein, a maize recombinant inbred population (RIL) was field grown to maturity across four envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 41 publications
(51 reference statements)
13
36
0
1
Order By: Relevance
“…The phenotypic associations, observed in our study, corroborate well with what we know about the biochemical composition of cereal grains and are in agreement with other studies of phenotypic associations within grain ionome of major cereals, such as sorghum (Shakoor et al , 2016), maize (Baxter et al , 2013; Gu et al , 2015), rice (Stangoulis et al , 2007), and wheat (Morgounov et al , 2007; Gomez-Becerra et al , 2010b; Pandey et al , 2016). Most of these studies reported positive associations of the essential metal microelements- Cu-Fe-Zn with GPC and S, and the essential metal macroelements Ca-K-Mg with P in cereal grains.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The phenotypic associations, observed in our study, corroborate well with what we know about the biochemical composition of cereal grains and are in agreement with other studies of phenotypic associations within grain ionome of major cereals, such as sorghum (Shakoor et al , 2016), maize (Baxter et al , 2013; Gu et al , 2015), rice (Stangoulis et al , 2007), and wheat (Morgounov et al , 2007; Gomez-Becerra et al , 2010b; Pandey et al , 2016). Most of these studies reported positive associations of the essential metal microelements- Cu-Fe-Zn with GPC and S, and the essential metal macroelements Ca-K-Mg with P in cereal grains.…”
Section: Discussionsupporting
confidence: 92%
“…Association analysis is increasingly used for identification of chromosomal regions affecting mineral accumulations (Alomari et al , 2017; Kumar et al , 2018), and ionomic traits (Shakoor et al , 2016; Ziegler et al , 2018). Yet, quantitative trait loci (QTL) analysis, based on segregating mapping populations, remains an important approach for genetic dissection of elemental accumulation (Gu et al , 2015; Velu et al , 2017; Huang et al , 2017). The recent development of wheat high-throughput SNP genotyping assays (Wang et al , 2014) and the assembly of reference genomes for wild emmer wheat ( Triticum turgidum ssp.…”
Section: Introductionmentioning
confidence: 99%
“…Natural variation of Fe (8.0 to 62 mg kg −1 ) and Zn (12.0 to 58.0 mg kg −1 ) has been extensively reported as a prerequisite for genetic biofortification [36,37]. However, a genetic approach may not always be adequate due to several interacting factors, including lack of readily available germplasm, unfavorable genetic, physiological, and chemical interactions within the ionome [38], and negative relationships with grain yield [17,20]. These perceived shortcomings of genetic biofortification recently led to promoting molecular breeding [38,39] as a means of improving [nutrient] and bioavailability of micronutrients in maize and other grain crops.…”
Section: Discussionmentioning
confidence: 99%
“…However, and despite their variable effects on nutrient densities and indices (Table 2), starch and protein, but not oil, clustered together in accordance with G(HG) differences (Figure 2). These relationships and cluster-affiliations may render selection of desirable trait combinations much easier; however, due to negative relationships, selection for some nutrient combinations (e.g., Cu and K with N or S; Figure 4) may be more difficult to achieve [17].…”
Section: Phenotypic Variation and Variance Componentsmentioning
confidence: 99%
See 1 more Smart Citation